Teenage mothers' knowledge of sex education in a general hospital of the Umtata district - CX Williams (AOSIS, 1999)
There has been growing concern about the increase in teenage pregnancies in relation to the teenagers' knowledge of human sexuality and the impact sex education has on these teenagers in both the urban and rural areas. The aim of the study was to assess the knowledge of sex education and the health beliefs of teenagers with regard to teenage pregnancy.